Luteolin alleviates inflammation and autophagy of hippocampus induced by cerebral ischemia/reperfusion by activating PPAR gamma in rats - Lu Li; Guanghua Pan; Rong Fan; Dalei Li; Lei Guo; Lili Ma; Hui Liang; Jiaoxue Qiu (BMC, 2022)
Abstract Background Luteolin, a flavonoid compound with anti-inflammatory activity, has been reported to alleviate cerebral ischemia/reperfusion (I/R) injury. However, its potential mechanism remains unclear. Methods The binding activity of luteolin to peroxisome proliferator-activated receptor gamma (PPARγ) was calculated via molecular docking analysis. Rats were subjected to middle cerebral artery occlusion and reperfusion (MCAO/R). After reperfusion, vehicle, 25 mg/kg/d luteolin, 50 mg/kg/d luteolin, 10 mg/kg/d pioglitazone, 50 mg/kg/d luteolin combined with 10 mg/kg/d T0070907 (PPARγ inhibitor) were immediately orally treatment for 7 days. ELISA, TTC staining, H&E staining, immunohistochemistry, immunofluorescence and transmission electron microscope methods were performed to evaluate the inflammation and autophagy in damaged hippocampal region. The PPARγ, light chain 3 (LC3) B-II/LC3B-I and p-nuclear factor-κB (NF-κB) p65 proteins expression levels in damaged hippocampal region were analyzed. Results Luteolin showed good PPARγ activity according to docking score (score = − 8.2). Luteolin treatment downregulated the infarct area and the pro-inflammatory cytokines levels caused by MCAO/R injury. Moreover, luteolin administration ameliorated neuroinflammation and autophagy in damaged hippocampal region. Pioglitazone plays protective roles similar to luteolin. T0070907 concealed the neuroprotective roles of 50 mg/kg/d luteolin. Conclusions Luteolin exerts neuroprotective roles against inflammation and autophagy of hippocampus induced by cerebral I/R by activating PPARγ in rats.